Soziale Marktwirtschaft in der digitalen Zukunft Foresight-Bericht - Strategischer Vorausschauprozess des BMWi - Holtmannspötter, Dirk; Heimeshoff, Ulrich; Haucap, Justus; Loebert, Ina; Busch, Christoph; Hoffknecht, Andreas (Wettbewerb und Regulierung von Märkten und Unternehmen, 2023)
This book contains the results of a strategic forecast conducted for the Federal Ministry of Economics on the implications of digitalisation for the social market economy with a time horizon until 2035. Foresight method-ology is used to develop road maps for eight key technologies as well as six scenarios on topics such as the platform economy, Industry 4.0, artificial intelligence and sustainability. Potential future impacts of digitalisa-tion are analysed, and economic and regulatory policy options are derived from this. This interdisciplinary cooperative project links expertise from futures research, economics, particularly com-petition economics, and law.